1980
DOI: 10.1007/bf01953756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tranylcypromine on the concentrations of some trace amines in the diencephalon and hippocampus of the rat

Abstract: Concentrations of 4 trace amines in diencephalon and hippocampus of the rat were measured by integrated-ion-current mass spectrometry after administration of the antidepressant drug, tranylcypromine. Much larger increases were observed for 2-phenylethylamine and tryptamine than for m- and p-tyramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…The brain concentrations of PEA obtained after administration ofCEPEA are similar to or greater than those reported after administration of MAO inhibitors (Boulton et al, 1973;Philips & Boulton, 1979;Philips et al, 1980;Baker et al, 1984). The administration of CEPEA did not markedly inhibit MAO activity, and this study demonstrates the feasibility of using a prodrug to increase the brain PEA concentrations.…”
Section: Discussionsupporting
confidence: 70%
“…The brain concentrations of PEA obtained after administration ofCEPEA are similar to or greater than those reported after administration of MAO inhibitors (Boulton et al, 1973;Philips & Boulton, 1979;Philips et al, 1980;Baker et al, 1984). The administration of CEPEA did not markedly inhibit MAO activity, and this study demonstrates the feasibility of using a prodrug to increase the brain PEA concentrations.…”
Section: Discussionsupporting
confidence: 70%
“…In summary, CEPEA administration caused sustained elevation of rat brain, blood and liver PEA concentrations, thus acting as a prodrug. The brain concentrations of PEA obtained after administration ofCEPEA are similar to or greater than those reported after administration of MAO inhibitors (Boulton et al, 1973;Philips & Boulton, 1979;Philips et al, 1980;Baker et al, 1984). The administration of CEPEA did not markedly inhibit MAO activity, and this study demonstrates the feasibility of using a prodrug to increase the brain PEA concentrations.…”
Section: Discussionsupporting
confidence: 70%
“…B. TA measurements were recorded 6 h after intraperitoneal (i.p.) injection of TCP/PLZ (Baker et al 1984), but peak TA concentrations may well have subsided by then: Philips et al (1980) demonstrated that, following i.p. TCP injection in the rat model, TA levels in both hippocampus and diencephalon peaked after roughly 45-90 min.…”
Section: Framing the Discussionmentioning
confidence: 99%